Analisis Risiko Keselamatan dan Kesehatan Kerja (K3) Dalam Pengelolaan Limbah Medis Rumah Sakit Islam Hasanah Muhammadiyah Mojokerto Di Masa Pandemi COVID-19 - Halik Wijaya; Muh. Khidri Alwi; Alfina Baharuddin (Journal of Muslim Community Health, 2021)
Background: The implementation of environmental sanitation in environmental media is carried out by processing hospital waste, namely infectious and non-infectious waste. The purpose of this study is to analyze more deeply about the risks of occupational safety and health (K3) in medical waste management of Hasanah Muhammadiyah Islamic Hospital in Mojokerto during the pandemic Covid-19. Methods: The type of research used in this research is quasi qualitative. The techniques used are observation, in-depth interviews (indepth interview) and documentation continuously during the research. Informants in this study are divided into three, namely key informants, namely the Head of the IPL (Waste Management Installation) unit, regular informants are part of the health worker and know the flow of the waste management system and are willing to be involved in research at Hasanah Muhammadiyah Hospital, Mojokerto, and supporting informants, namely cleaning services. Working in the sewage treatment department. Results: From the results of the study, it was found that the Covid-19 medical waste processing carried out at the RSHIMM was still the same as ordinary medical waste processing, where the waste treatment process started from sorting, holding according to the yellow container. Risk of accidents found, Ramp used to transport waste medical, patients and corpses are still in the same line, and cleaning services also have not used special clothes when transporting waste and medical waste sharp objects still use open artificial cardboard. Conclusion: Risk control is carried out by complying with SOPs, but is still constrained by the lack of infrastructure.